Phospholipid bilayers as biomembrane-like barriers in layer-by-layer polyelectrolyte films - Pilbat, Ana-Maria (Langmuir : the ACS journal of surfaces and colloids, 2007)
Dipalmitoylphosphatidylcholine (DPPC) bilayer was created on the surface of an exponentially growing poly(glutamic acid)/poly(lysine) (PGA/PLL) layer-by-layer polyelectrolyte film. The lipid bilayer decreased the surface roughness of the polyelectrolyte film. The layer-by-layer construction of the polyelectrolyte film could be continued on the top of the DPPC layer. The lipid bilayer, however, formed a barrier in the interior of the polyelectrolyte film, which blocked the diffusion (a prerequisite for exponential growth) of the polyelectrolytes. Thus, a new growth regime started in the upper part of the polyelectrolyte film, which was added to embed the DPPC bilayer. The structure and the dynamics of the DPPC bilayer on the polyelectrolyte film surface remained similar to that of its hydrated multibilayers, except that the phase transition became wider. In the case of embedded DPPC bilayers, in addition, the phase-transition temperature also decreased. This is the result of interactions with the nonconcerted movements of the barrier-separated lower and higher parts of the polyelectrolyte film. Gramicidin A (GRA) as a model of lipid-soluble peptides and proteins was successfully incorporated into such DPPC films. The DPPC films, either with or without GRA, were remarkably stable; as many heating-cooling cycles to measure phase transition could be carried out without visible alterations as wanted